Effect of Storage Methods and Management of Sweet Potato on the Incidence of Tuber Rot Induced by Rhizopus stolonifer in Kano, Nigeria - Edun, Bolanle Tolani; Lurwanu, Yahuza; Sunusi, Mustapha; Aliyu, Rabi’u Shehu (Journal of Tropical Crop Science, 2019)
Different storage methods and management practices of sweet potatoes in Kano state, northwestern Nigeria, were investigated to fi nd out how they may affect the incidence of tuber rot. Three local government areas were selected for the sample collection. In each local government area, two sweet potato farming communities were selected, infected and uninfected tubers were sampled and taken to the laboratory for further studies. Pathogenicity test confi rmed Rhizopus stolonifer as the causal pathogen responsible for tuber rot and this fungus was used for the inoculation of fresh sweet potato tubers in all the storage and management methods used in the experiment. Tubers preserved using ash + sand and fungicide + sand showed the least incidence of tuber rots. Similarly, it was also observed that storage of tubers with sand alone showed a reduction in the severity of the disease across the storage weeks. There was no signifi cant difference in the incidence and severity of tuber rot between the two inoculation methods with both the treatment combinations. Our result showed that the incubation period of R. stolonifer to infect sweet potato tubers started at two days after inoculation with about 25% infection. The result also indicated that none of the tubers treated with fungicide, ash, and eucalyptus sprouted at both the storage weeks, this may be attributed to the possibility of having some inhibitory properties against sprouting.